Nuclear magnetic resonance spectroscopy : an introduction to principles, applications, and experimental methods /: an introduction to principles, applications, and experimental methods. (2018) - Lambert, Joseph B; Mazzola, Eugene P; Ridge, Clark, 1980-
No abstract available